Formulation & Evaluation of Cream of Suhaga & Salicylic Acid for Acne Treatment - Raj, Himanshu; Sharma, Pankaj; Jain, Vinay (Journal of Neonatal Surgery, 2025)
Background: Acne is a widespread skin condition primarily affecting teenagers & young adults, resulting from alterations in the pilosebaceous glands. It presents with inflammation, the formation of comnones, and bacterial growth, with hormonal, dietary, and environmental influences playing a role. Although acne is typically self-limiting, it can cause significant scarring and emotional distress. This study aimed to develop & assess creams containing both natural & synthetic ingredients for acne treatment, focusing on their physicochemical properties and their compatibility with the skin's natural pH. Methods and Materials: We prepared four cream formulations (F1, F2, F3, F4) using stearic acid, beeswax, almond oil, purified water, glycerin, potassium hydroxide (KOH), suhaga, salicylic acid, castor oil, phenoxyethanol, and rose oil. The production process involved several steps: blending oil and water components, adding active ingredients, and mixing preservatives and fragrances. Each formulation was evaluated for homogeneity, color, pH, spreadability, smear type, washability, and viscosity characteristics. Results: The formulations displayed different physicochemical properties depending on their compositions. F4 showed the best spreadability (7.06 cm²), the lowest viscosity (4300 Pa·s at 60 S⁻¹), and excellent washability. In terms of pH, F1 (4.3) and F2 (5.6) were close to the skin's physiological pH range (4.5–5.5), indicating good compatibility. Physical assessments showed improvements in homogeneity, color, and after-feel from F1 to F4, correlated with increased water content and reduced percentages of wax and stearic acid. Conclusion: This study underscored the significant impact of formulation differences on the properties of the creams. F4 was identified as the most promising formulation owing to its exceptional spreadability, homogeneity, washability, and moisturizing effects. Nevertheless, F2 emerged as the most compatible with physiological skin conditions due to its optimal pH and balanced physicochemical properties, suggesting a need for further studies to enhance its efficacy in treating acne.